Residual stresses reconstruction in shot peened specimens containing sharp and blunt notches by experimental measurements and finite element analysis. (June 2016) - Benedetti, M.; Fontanari, V.; Winiarski, B.; Allahkarami, M.; Hanan, J.C.
Highlights: Notched specimens were subjected to controlled shot peening. Residual stresses were measured along the notch bisector. Two complimentary experimental techniques were used. The measurements were used to reconstruct the residual stress field. Residual stresses are concentrated at the tip of the sharper notches. Abstract: The knowledge of the residual stress (RS) field in the vicinity of a notch is of paramount importance to understand the fatigue resistance of shot peened components containing such stress raisers. In the first part of this work (Winiarski et al. 2016, Exp. Mech.), RS were measured along the notch bisector using non-destructive and destructive techniques, namely micro-XRD and FIB-SEM DIC micro-slot cutting (μSC) and micro-hole drilling (μHD). These indicate an increasing concentration of the longitudinal residual stress component with increasing sharpness of the notch. In this paper, these linescan measurements are used to reconstruct the complete RS field through finite element (FE) analyses. Specifically, RSs are introduced into the FE model using thermal misfit strains (eigenstrains), whose intensity and spatial distribution are deduced by fitting the experimental data. Since the eigenstrains depend on the actual notch geometry, their distribution cannot be estimated from residual stress distributions measured on plain or notched specimens of different geometry. The proposed approach can be very useful to estimate the notch fatigue resistance of shot peened components on the basis of local stress and fracture mechanics approaches.